2005
DOI: 10.1080/17457300500089954
|View full text |Cite
|
Sign up to set email alerts
|

Safe Community in different settings

Abstract: This paper describes the Safe Community concept and how communities aspired to safety through a structured, collaborative approach rather than a community that is already perfectly safe. The Safe Community movement started in Sweden at the end of the 1980s and was based on community-based injury prevention activities. Safe Communities are the communities that meet a set of 12 criteria (later changed to six indicators) set out by the WHO Collaborating Centre (WHO CC) on Community Safety Promotion at Karolinska … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…This process has been successful as it allows for the collective analysis of information by a group, bringing together the group's experience and knowledge in a cooperative manner that promotes local capacity. By engaging the community to develop contextspecific prevention strategies, community members are empowered in the decision-making process and their capacity for problem-solving can also be enhanced, along with the ability for collective decision-making and collective action (Rahim 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This process has been successful as it allows for the collective analysis of information by a group, bringing together the group's experience and knowledge in a cooperative manner that promotes local capacity. By engaging the community to develop contextspecific prevention strategies, community members are empowered in the decision-making process and their capacity for problem-solving can also be enhanced, along with the ability for collective decision-making and collective action (Rahim 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Engagement of community members in safety promotion programs shows that people not only live and work in the community, but also accept a social responsibility to identify the community's needs, problems, and potential to prevent injuries (19). sufficient and inconsistent evidence on the effectiveness of safe communities, which makes it difficult to draw a definite conclusion in this area (27).…”
Section: Discussionmentioning
confidence: 99%
“…Designated safe communities implement injury prevention programs in an intersectoral structure for safety promotion in all populations (9,19). In a study by Svanstrom et al on designated safe communities, established before 2005, inconsistency was reported in reports, approaches, and methods of safety promotion in communities (20).…”
Section: Introductionmentioning
confidence: 99%
“…The ''Safe Community''-idea, was later incorporated in a strategy within the global network of the World Health Organisation (WHO) for injury prevention and within the national programme for injury prevention of the Swedish Public Health Institute. The basic idea in ''A Safe Community'' includes a series of criteria in such a community and has principles on how to put together the work within the structure and organisation existing in the municipality (Cho and Svanström, 2002;Green et al, 2001;Leung et al, 2004;Lindquist et al, 2004;Nielsen et al, 2006;Pain and Townshend, 2001;Rahim, 2005).…”
Section: Community-based Promotion Of Safety At the Municipal Levelmentioning
confidence: 99%
“…The WHO Safe Community network had been operating for 16 years in 2005, involving SCs in 16 countries, and the network has 15 affiliated support centres around the world (Rahim, 2005). Within the research into ''A Safe Community'', the strategy and its realisation describes municipalities and countries that have employed law enforcement as an important top-down strategy at the national level in combination with the bottom-up strategies within ''A Safe Community'' (Cho and Svanström, 2002;Leung et al, 2004;Welander et al, 2001).…”
Section: Community-based Promotion Of Safety At the Municipal Levelmentioning
confidence: 99%